Agonistic planning theory revisited: The planner's role in dealing with conflict - Manfred Kühn (Planning Theory, 2020)
Approaches from agonistic planning theory view conflict as immanent to pluralistic democracies and criticize communicative planning theories for disregarding such conflict and relying too much on consensus and cooperation. This criticism has led to a partial division between agonistic and communicative planning theories. The article presents the basic principles of agonistic planning theory and develops a criticism of its biasedly positive view of conflict as a productive force, as well as the significant gap between its theory and practice. In order to expand the scope of planning and to bridge this gap between theory and practice, the article distinguishes between three ideal types of dealing with conflict: (a) avoidance of conflict that is understood as disruptive, (b) conflict as an occasion for participation and consensus building, and (c) acceptance of conflict. These passive, reactive, and proactive manners of dealing with conflict are assigned to the comprehensive-rationalistic, communicative, and agonistic planning theories. Because these ideal types occur in practice in various mixed forms, the theoretical framework may help to understand and analyze the politics of planning. Finally, the article presents some planning challenges and dilemmas with regard to the ongoing transition towards pluralist democracies.
Keywords: 300; agonism; conflict; participation; planning theory; pluralism